PEMBINAAN KEMANDIRIAN SANTRI PONDOK PESANTREN MIFTAHUL HUDA AL-HASAN MELALUI PROGRAM KEWIRAUSAHAAN MORING - Lestari, Wina (IKIP Siliwangi, 2025)
The background of this research is that entrepreneurship education is needed by the students as a provision after they return to their respective areas, however the management of the moring entrepreneurship program at the Miftahul Huda Al-Hasan Islamic boarding school is still lacking, this can be seen from the lack of supervision of the students' independence. The aim of this research is to identify the process of fostering the independence of students at the Miftahul Huda Al-Hasan Islamic boarding school through the moring entrepreneurship program. The theory used in this research is the concept of fostering independence, entrepreneurship, and Islamic boarding schools. The research uses qualitative research methods so that the approach used is a qualitative descriptive approach. Interviews, observation and documentation were used as data collection techniques in this research. The research location was at the Miftahul Huda Al-Hasan Islamic boarding school. The respondents were one manager, one educator and 5 students. Based on research results, the results of entrepreneurship coaching are that 90% of students master it before receiving coaching, students have difficulty in the process, but when they are given coaching, students begin to know and learn to do it.